2016
DOI: 10.1074/jbc.m116.734012
|View full text |Cite
|
Sign up to set email alerts
|

A Hidden Active Site in the Potential Drug Target Mycobacterium tuberculosis dUTPase Is Accessible through Small Amplitude Protein Conformational Changes

Abstract: Edited by Norma AllewelldUTPases catalyze the hydrolysis of dUTP into dUMP and pyrophosphate to maintain the proper nucleotide pool for DNA metabolism. Recent evidence suggests that dUTPases may also represent a selective drug target in mycobacteria because of the crucial role of these enzymes in maintaining DNA integrity. Nucleotide-hydrolyzing enzymes typically harbor a buried ligand-binding pocket at interdomain or intersubunit clefts, facilitating proper solvent shielding for the catalyzed reaction. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 69 publications
(93 reference statements)
1
8
0
Order By: Relevance
“…In the equation F 0 is the unquenched and F is the quenched tryptophan fluorescence, Q is the quencher (acrylamide), K sv is the dynamic (bimolecular) quenching constant and V is the static (sphere of action) component of quenching [42,43,44].…”
Section: Methodsmentioning
confidence: 99%
“…In the equation F 0 is the unquenched and F is the quenched tryptophan fluorescence, Q is the quencher (acrylamide), K sv is the dynamic (bimolecular) quenching constant and V is the static (sphere of action) component of quenching [42,43,44].…”
Section: Methodsmentioning
confidence: 99%
“…However, when considering buried protein pockets and cavities in general, such seemingly trivial displacements may be of significance. Recent molecular dynamics simulations and experiments have suggested that large-scale side chain or secondary structure conformational changes are not a prerequisite for ligand binding to buried cavities but rather subtle and rapid movement of peptide structural elements can be sufficient to facilitate ligand ingress and egress (47)(48)(49)(50). Although beyond the scope of this work, we speculate that the effects of any subtle movement of structural elements may propagate within AfGna1 and be important for ligandbinding dynamics to the unusual buried dimer interface pocket.…”
Section: Targeting a Critical Step In Fungal Hexosamine Biosynthesismentioning
confidence: 81%
“…EDTA seems to preferably bind to one of the entrances of the polar central channel of hDUT (Figure 3 A–B) while it only weakly populates the corresponding apolar area in mtDUT in the docking runs (Figure 3 C–D). Considering the enzymatic mechanism, EDTA binding to the outer central channel may not have great or any effect on the enzymatic activity as this part have not shown significant conformational changes in previous studies [55,74]. On the other hand, EDTA may perturb the interaction of the C-terminal arm with the protein core as this contact surface is the first and second most populated EDTA binding site in mtDUT and hDUT, respectively, in the docking simulations (Figure 3).…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, EDTA may perturb the interaction of the C-terminal arm with the protein core as this contact surface is the first and second most populated EDTA binding site in mtDUT and hDUT, respectively, in the docking simulations (Figure 3). The intact C-terminal arm–protein core interaction is necessary for the hydrolysis to occur as this interaction provides the shielding of the active site from the solvent [52,57,74]. The differences in the predicted EDTA-protein interactions, especially at the C-terminal arm can explain the observed differences in EDTA-inhibited dUTPase activities between hDUT and mtDUT.…”
Section: Discussionmentioning
confidence: 99%